Pemanfaatan PLN Mobile Sebagai Solusi Digital Untuk Kemudahan Pelanggan Dalam Layanan Kelistrikan PT PLN UP3 Pinrang - Muhammad Nur; Kasma Hafid; Rahmatillah Rahmatillah; Harianti Harianti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
In the digital era, PT PLN launched the PLN Mobile application to enhance service efficiency for customers. This application facilitates customers in accessing information such as electricity bills, disturbance reports, and outage schedules without the need to visit PLN offices. This study aims to evaluate the utilization of the PLN Mobile application at PT PLN UP3 Pinrang, identify challenges faced, and formulate relevant solutions. The research method used is qualitative descriptive with an approach including interviews, observations, and documentation. The results of the study show that although the application provides convenience, challenges such as customers’ lack of understanding in using the application and technical issues remain obstacles. To address these issues, outreach and the provision of simple guides were conducted to improve customer understanding. Overall, the application has positively contributed to enhancing the quality of service and operational efficiency at PLN.